Shir, Syrien: Die Arbeiten des Jahres 2014 - Dietrich, Laura; Tvetmarken, Cecilie Lelek (e-Forschungsberichte des DAI, 2023)
The Late Neolithic site of Shir near Hama was extensively excavated between 2005 and 2010. Central issues within the research program were aspects of the development of the settlement and the relationship between the settlement and the surrounding area. The analysis of the excavation data currently being conducted provides a picture of a complex society in one of the core regions for the Neolithization process in the Near East. The results will allow a better understanding of settlement activities during the 7th millennium BCE in the Northern Levant.